Pengaruh Strategi Pomosi Terhadap Keputusan Konsumen Menggunakan Go-Car Pada PT. Gojek Indonesia Kota Palembang - Tutik Pebrianti; Zein Ghozali; Hilwa Anggraini; Vivin Afini (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2018)
Companies must be able to compete with competitors to improve services to consumers. Promotion strategies must still be carried out to attract consumers to keep choosing Go-Car as transportation choice. Researcher is interested in conducting research on the effect of promotion strategies on consumer decisions using Go-Car in Palembang. The population is the people in Palembang. Samples taken in this study are 80 respondents using cluster sampling method, with the help of SPSS softare version 16. The results of this study indicate that partially there is a positive and signifi cant influence on consumer decisions using Go-Car in Palembang.This can be seen from t value of 2.530> t table of 1.990 and the significance value of0.001, then t count > t table and the significance value <0.05 which means that promotion strategies variable (X) significantly influences the decision on the usage variable (Y) . This also means that promotion strategiesvariable shows how promotion strategies of PT. Go-jek Indonesia are able to convince the people of Palembang to use Go-Car services.